Nanometer‐scale characterization of exceptionally preserved bacterial fossils in Paleocene phosphorites from Ouled Abdoun (Morocco). Issue 2 (10th January 2013) - Cosmidis, J.; Benzerara, K.; Gheerbrant, E.; Estève, I.; Bouya, B.; Amaghzaz, M.
Abstract Micrometer‐sized spherical and rod‐shaped forms have been reported in many phosphorites and often interpreted as microbes fossilized by apatite, based on their morphologic resemblance with modern bacteria inferred by scanning electron microscopy (SEM) observations. This interpretation supports models involving bacteria in the formation of phosphorites. Here, we studied a phosphatic coprolite of Paleocene age originating from the Ouled Abdoun phosphate basin (Morocco) down to the nanometer‐scale using focused ion beam milling, transmission electron microscopy (TEM), and scanning transmission x‐ray microscopy (STXM) coupled with x‐ray absorption near‐edge structure spectroscopy (XANES). The coprolite, exclusively composed of francolite (a carbonate‐fluroapatite), is formed by the accumulation of spherical objects, delimited by a thin envelope, and whose apparent diameters are between 0.5 and 3 μm. The envelope of the spheres is composed of a continuous crown dense to electrons, which measures 20–40 nm in thickness. It is surrounded by two thinner layers that are more porous and transparent to electrons and enriched in organic carbon. The observed spherical objects are very similar with bacteria encrusting in hydroxyapatite as observed in laboratory experiments. We suggest that they are Gram‐negative bacteria fossilized by francolite, the precipitation of which started within the periplasm of the cells. We discuss the role of bacteria in the fossilization mechanism and propose that they could have played an active role in the formation of francolite. This study shows that ancient phosphorites can contain fossil biological subcellular structures as fine as a bacterial periplasm. Moreover, we demonstrate that while morphological information provided by SEM analyses is valuable, the use of additional nanoscale analyses is a powerful approach to help inferring the biogenicity of biomorphs found in phosphorites. A more systematic use of this approach could considerably improve our knowledge and understanding of the microfossils present in the geological record.